2011
DOI: 10.1007/s10059-011-2315-5
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of Oct4 in Human Esophageal Squamous Cell Carcinoma

Abstract: The Octamer 4 gene (Oct4) is a master pluripotency controller that has been detected in several types of tumors. Here, we examine the expression of Oct4 in human esophageal squamous cell carcinoma (ESCC). We found that punctate Oct4 protein was expressed in most (93.7%) ESCC samples but it was not observed in esophageal mucosa. Some ESCC cells had the capacity to form tumorospheres; those with an Oct4 + -rich cell phenotype had increased proliferation and Oct4 mRNA levels compared to those of differentiated ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…A previous study showed that overexpression of OCT4 in ESCC has been consistently associated with cancer proliferation, metastasis, and drug resistance 22. In the present study, based on the analysis of 95 ESCC patient samples with complete follow‐up data, the LEF1 expression level in ESCC was higher than that in adjacent tissue, and the high expression of LEF1 in patients was strongly associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…A previous study showed that overexpression of OCT4 in ESCC has been consistently associated with cancer proliferation, metastasis, and drug resistance 22. In the present study, based on the analysis of 95 ESCC patient samples with complete follow‐up data, the LEF1 expression level in ESCC was higher than that in adjacent tissue, and the high expression of LEF1 in patients was strongly associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies have shown that the expression of OCT4 is increased to a variable extent in tumor specimens from patients with ESCC 22. However, no studies have reported on LEF1 expression and its relationship with clinicopathological features in ESCC.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have found that Sox2 might promote cell proliferation and tumorigenesis of breast cancer [10], and Oct3/4 might associated with the early stage of pancreatic cancer carcinogenesis [11,12], and even correlated with lymph node metastasis in colorectal cancer cells [13]. High expression of OCT-4 has been observed in esophageal cancer [14], suggesting association between OCT-4 and proliferation of esophageal cancer.…”
Section: Introductionmentioning
confidence: 93%
“…18,19 There have been studies that reported that Oct4 is overexpressed in many kinds of cancers, such as, lung cancer, oral squamous cell carcinoma, GC, breast cancer, and esophageal cancer and ectopic expression may play a role in the improvement of disease. [20][21][22][23] Nevertheless, there is little relation between MUC5AC and Oct4 with clinical factors in GC, and contradictory findings have been reported. In addition to clinical outcome, lymph node and distant metastasis has been shown to be important factors for prognostic in GC.…”
Section: In Addition Low Expression Of Muc5ac and High Expression Ofmentioning
confidence: 99%